UNVEILING ASTROTOURISTS’ PROFILES. ACTIVITIES, MOTIVATIONS, ECONOMIC AND SOCIAL BENEFITS AND EXPERIENCES - Solano-Sánchez, Miguel Ángel; Aja-Valle, Jaime; Arteaga-Sánchez, Rocío; López-Guzmán, Tomás (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2024)
This research aims to determine the variations that occur in the socio-demographic profile (gender, age, educational level and income) of the visitor interested in astrotourism based on some questions about the activities they carry out related to astronomy, motivations, economic and social benefits and the assessment of experiences about astrotourism through data gathered by a questionnaire. An artificial neural network is developed to generate potential “identikits” or estimated profiles of astrotourists based on the replies incorporated into the model and easily customisable by the researcher, this being especially useful in the development of products and services adapted to astrotourism.